Reaching out to the world - New Straits Times, (2011)
IT is not often one gets to witness academic history in the making, given that the audacity to propose an idea that would change the foundations of learning and the integrity to follow through with its implementation is a rare thing nowadays - more so when what is proposed is concerned with catering to the bigger picture of public good rather than confined to the sweatshop of profit.